2020
DOI: 10.1155/2020/6680384
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation on Improvement Performance of Waved Connection to Reduce Damage on Buried Gas Pipeline

Abstract: One of the major challenges for the oil and gas industry is to keep buried metal pipes safe from faulting. This paper discusses about a solution to keep buried pipes safe. In this study, after examining the different dimensions of the effect of wave connection on improving the performance of buried metal pipes, by changing the geometric shape of the wave connection such as doubling it, the behavior of the pipe is greatly improved. Waved connections, by their local deformation, create a rotational joint in a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Of course, these relations are also interchangeable. e maximum amount of particle displacement (x) in terms of meters, at a distance of R (meters) from the source of the explosion, entirely or relatively buried, can be estimated from relation (22), where w is the mass of the explosive material in kilograms, c is the seismic wave velocity in meters per second, f c is the coupling coefficient, calculated from Figure 9, and n is the dimensionless reduction coefficient; from Table 3, it is obtained that [19] x w (1/3)…”
Section: Study Of the Propagation Of Blast Waves In The Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, these relations are also interchangeable. e maximum amount of particle displacement (x) in terms of meters, at a distance of R (meters) from the source of the explosion, entirely or relatively buried, can be estimated from relation (22), where w is the mass of the explosive material in kilograms, c is the seismic wave velocity in meters per second, f c is the coupling coefficient, calculated from Figure 9, and n is the dimensionless reduction coefficient; from Table 3, it is obtained that [19] x w (1/3)…”
Section: Study Of the Propagation Of Blast Waves In The Soilmentioning
confidence: 99%
“…In this method, the normal contact of two levels with the hard contact method is considered to prevent the surfaces from sinking into each other. Also, the tangential interaction of the two surfaces with a friction coefficient of 0.5 that was suggested by Vasouras and Kolbadi [21,22] is regarded in the analyzes. is number is a suitable value for the interaction of soil with metal structures.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Breakdowns resulting from fatigue are a major concern in engineering design [27]. Economic costs of the failure and its prevention are very high, and it is taken into consideration that nearly 80% of these costs include the situations that cyclic loading and fatigue are at least one contributing factor [28]. erefore, the annual cost of material fatigue to the U.S economy is nearly 3% of the GDP and the same percentage is anticipated for other industrial countries.…”
Section: Fatigue Failure Criterionmentioning
confidence: 99%
“…On the other word, by increasing the available opportunity for doing the activity without worry about the condition of the fatigue of the pipe, cost of missed opportunity can be decreased and the costs resulting from servicing at other places can be investigated to increase profitability to the employer. Alternatively, it can be to answer this basic question whether it is correct to use a cross model in studies such as in [17,28]. Given the abovementioned graph, it can be said that by considering the bed as a cross, there will be no significant difference in the answers.…”
Section: Elasticity Modulus Of the Soil Bedmentioning
confidence: 99%
“…e results of the specimens showed that this process caused nonlinear behavior in these types of hybrid composite bars [23]. Since few tests have been performed on evaluating the performance of hybrid composite bars in concrete elements, in this research project, four specimens of concrete beams reinforced with hybrid composite bars were investigated under statistical four-point flexural tests [24]. Moreover, results were compared with 2 specimens of beams reinforced with steel bars.…”
Section: Introductionmentioning
confidence: 99%